1978
DOI: 10.1017/s0022172400025146
|View full text |Cite
|
Sign up to set email alerts
|

Contaminated roof-collected rainwater as a possible cause of an outbreak of salmonellosis

Abstract: SUMMARYRoof-collected rainwater is a common water source in subtropical regions and has not been associated with human illness. In Trinidad, the West Indies, a church group, attending a rural camp, developed gastrointestinal illness, caused by Salmonella arechevalata. This rare serotype was isolated from stool specimens of campers, foods eaten at the camp, and a water tap, which was supplied by a storage tank of roof-collected rainwater. The surface of the roof, used as water catchment, was covered with bird f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
4

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 7 publications
0
32
0
4
Order By: Relevance
“…Although both genera of bacteria lead predominantly host-associated lifestyles, they can persist in water sources, which act as bacterial reservoirs facilitating transmission between hosts. Koplan et al (1978) reported a case study of contaminated roof-collected rainwater behind an outbreak of salmonellosis in the Caribbean. In this case, the surface of the roof used as water catchment was covered with bird feces that where washed off, thus contaminating the rainwater harvesting that was destined to drinking purposes without any treatment.…”
Section: Bacteria and Pathogensmentioning
confidence: 99%
“…Although both genera of bacteria lead predominantly host-associated lifestyles, they can persist in water sources, which act as bacterial reservoirs facilitating transmission between hosts. Koplan et al (1978) reported a case study of contaminated roof-collected rainwater behind an outbreak of salmonellosis in the Caribbean. In this case, the surface of the roof used as water catchment was covered with bird feces that where washed off, thus contaminating the rainwater harvesting that was destined to drinking purposes without any treatment.…”
Section: Bacteria and Pathogensmentioning
confidence: 99%
“…The most likely agents of microbiological contamination of rooftop rainwater harvests are microorganisms that come through the droppings of birds, rodents, reptiles, and insects (Beysens et al, 2006;Koplan et al, 1978;Merritt et al, 1999). These include some species of Salmonella though S. typhi, which causes typhoid, isn't likely to be present as it is restricted to human hosts.…”
Section: Polkowska Et Al 2009mentioning
confidence: 99%
“…Another possible source of faecal streptococci is contamination from faeces of lizards and cockroaches which find their way to the basement tank. Serious health hazards from lizards, cockroaches and bird droppings is unlikely, although in rare cases salmonella in bird droppings may be conveyed to human beings [5]. Table 5 shows that only 67.6% and 12.7% of the samples collected from the Dar es Salaam city water supply distribution system were free from faecal coliforms during dry and rainy seasons respectively.…”
Section: Bacteriological Qualitymentioning
confidence: 99%